The Recovery of Maintenance in the EU and Worldwide - Beaumont, Paul; Hess, Burkhard; Walker, Lara; Spancken, Stefanie (Studies in Private International Law, 2014)
Cover; Half-title; Title; Copyright; Foreword; Editors' Preface; Contents; List of Contributors; Part One: Comparative Context; 1 Cultural Dimensions of Maintenance Law from a Private International Law Perspective; I. Introduction; II. Private International Law; III. Distinction between Spousal and Child Maintenance; IV. Concluding Remarks; Part Two: International Perspective; 2 Introduction to Part Two (International) and Part Three (International and EU); I. International; II. International and EU